2021
DOI: 10.1039/d1na00248a
|View full text |Cite
|
Sign up to set email alerts
|

Unique emissive behavior of combustion-derived particles under illumination with femtosecond pulsed near-infrared laser light

Abstract: Exposure to combustion-derived particles (CDPs), such as carbonaceous particulate matter (PM), has adverse effects on human health. Hence, selective detection of these particles in biological environments is required to understand...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The emission spectra of CB show a broadband emission from 380 to 700 nm with the emission intensity increasing at higher emission wavelengths. This is due to the unique WL emission from CB when illuminated using fs-pulsed nIR lasers. , The emission spectra of BrC show different behavior than CB; their response has four main features: (1) a strong third harmonic generation (THG) signal at 435 nm, (2) a weak, broad visible light emission (450–650 nm), (3) a weak second harmonic generation (SHG) signal at 650 nm, and (4) a broad, two-photon excited, autofluorescence (2PAF) signal (>650 nm).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The emission spectra of CB show a broadband emission from 380 to 700 nm with the emission intensity increasing at higher emission wavelengths. This is due to the unique WL emission from CB when illuminated using fs-pulsed nIR lasers. , The emission spectra of BrC show different behavior than CB; their response has four main features: (1) a strong third harmonic generation (THG) signal at 435 nm, (2) a weak, broad visible light emission (450–650 nm), (3) a weak second harmonic generation (SHG) signal at 650 nm, and (4) a broad, two-photon excited, autofluorescence (2PAF) signal (>650 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The capabilities of the setup were tested using CB and the corresponding phasor plot shows that CB has an instantaneous temporal response in line with the expected WL emission (Figure S16). , The weak broad emission from BrC-HA is not instantaneous and the lifetimes indicate that it arises from 3PAF. Similar observations were made for the emission from BrC-HASS, BrC-lignin, and BrC-SRFA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have reported that CDCPs can be detected in biological samples based on their unique white light (WL) emission under illumination with femtosecond (fs) pulsed near-infrared (NIR) lasers. 23,24 In this work, we present the development of dual-channel multiphoton flow cytometry (DCMPFC) setup, which combines light scattering with the unique WL emission from individual CDCPs passing through the focal spot of a fs-pulsed NIR laser for their label-free detection, quantification, and size estimation in a sheathed flow. The unique WL emission acts as a specific marker indicating the presence of CDCPs, whereas scattering detection can be used for their size estimation.…”
Section: Introductionmentioning
confidence: 99%